TEAM SPORTS AND BODY CULTURE: IMPACTS ON LEARNING AND MOTOR DEVELOPMENT (REMUNOM, 2025)
This study investigates the impacts of team sports on children's motor development and learning, emphasizing the importance of body culture in pedagogical practices. The research addresses the relationship between team sports activities and the improvement of fundamental motor skills, such as coordination and balance, in addition to exploring psychosocial benefits, such as teamwork and cooperation. The analysis of sports initiation programs in schools reveals how sports contribute to the comprehensive development of students, promoting not only physical development, but also inclusion and the construction of social values. Based on studies and evidence from authors such as Gallahue et al. (2013) and Menézes et al. (2014), this article proposes reflections on best practices and the need for appropriate pedagogical planning, considering the particularities of each student and group.Keywords: team sports; motor development; inclusion.